2022
DOI: 10.3390/jfb13010032
|View full text |Cite
|
Sign up to set email alerts
|

Dental Poly(methyl methacrylate)-Based Resin Containing a Nanoporous Silica Filler

Abstract: Poly(methyl methacrylate) (PMMA)-based resins have been conventionally used in dental prostheses owing to their good biocompatibility. However, PMMA-based resins have relatively poor mechanical properties. In the present study, a novel nanoporous silica filler was developed and introduced into PMMA-based resins to improve their mechanical properties. The filler was prepared by sintering a green body composed of silica and an organic binder, followed by grinding to a fine powder and subsequent silanization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Figure 1 showed the SEM micrographs of the experimental CRs, and it could be seen that nano-fillers distributed well over the whole surface of resin matrix. Good dispersibility of fillers was attributed to the mechanical strength of CRs [31]. As presented in Table 1, the three-point bending test showed that the addition of F-zirconia fillers could maintain the flexure strength of experimental CRs.…”
Section: Discussionmentioning
confidence: 83%
“…Figure 1 showed the SEM micrographs of the experimental CRs, and it could be seen that nano-fillers distributed well over the whole surface of resin matrix. Good dispersibility of fillers was attributed to the mechanical strength of CRs [31]. As presented in Table 1, the three-point bending test showed that the addition of F-zirconia fillers could maintain the flexure strength of experimental CRs.…”
Section: Discussionmentioning
confidence: 83%
“…Vojdani et al improved hardness by 13% with the addition of 5 wt% of alumina to PMMA [ 24 ]. Hata et al reported a more than 100% increase in hardness with 23% of nanoporous silica [ 25 ]. On the other side, Alhotan et al achieved only a 10% hardness increase with 7% of nano-zirconia [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…PMMA, as a transparent thermoplastic, has been developed to be a dental composite material reinforced with various fillers, such as particle, fiber, and particle-fiber. Different filler types have been reported in dental applications, such as TiO 2 [3], ZrO 2 [4], Al 2 O 3 [5], SiO 2 [6,7], and biomaterials of eggshell, seashell, and fish scale [8][9][10] for particle fillers, and natural and synthetic fibers [11,12]. However, there have been only a few studies on the particle-fiber combination, particularly the microcrystalline cellulose (MCC) particles-natural fiber.…”
Section: Introductionmentioning
confidence: 99%